O ensino de Filosofia no ensino fundamental: formação e contraconduta - Rocha, João Luiz de Souza (Universidade Federal do Tocantins, 2021)
The present research aims to investigate the concrete situation of the teaching of Philosophy implanted and developed over eleven years in the Full Time School Padre Josimo Moraes Tavares, the first municipal public school in the city of Palmas-Tocantins to adopt the discipline of philosophy among the components of the diversified part of its curriculum structure. For this, we adopt the problematization proposed by Michel Foucault as a theoretical-methodological presupposition, seeking to find conceptual tools to answer the questions and concerns that arose from the teaching experience at school. We traced an investigative trajectory between philosophy and its teaching, in an attempt to understand the role that the discipline of philosophy has in elementary education in a specific school environment. We work on several Foucaultian notions, such as relations of power, resistance, conduct, counterconduct, modes of objectification, modes of subjectivation, modes of subjection and governance of childhood. The possibility of critical reflection offered by the teaching of philosophy in the school evidences the own school institution as a territory of struggle and disputes in a political understanding of the role of philosophy teaching beyond the cognitive efficiency and the transmission of knowledge. It is about thinking and rethinking philosophy teaching with children and adolescents and their own field of activity, the school institution. The notion of Foucauldian government, understood as conducting the conduct of the other and of itself, leads us to a key interpretative teaching of philosophy that breaks with the idea that there is no escape from the process of assujeitamento promoted by the school. We seek to show open possibilities for another behavior, from the conscious relationship between teachers and students who critically reflect their own concrete conditions of existence. In this way, we try to think of a philosophy teaching as a counterconduct, in order to establish an experience of philosophy that promotes, through criticism, creativity in thinking, dialogue, listening, and self-transformation of those involved. The product presented was the elaboration and analysis of a didactic sequence of contents focused on a Teaching of Philosophy as counterconduct.